Value of Fast MVO Identification From Contrast-Enhanced Cine (CE-SSFP) Combined With Myocardial Strain in Predicting Adverse Events in Patients After ST-Elevation Myocardial Infarction - Zhang, Min; Lu, Yuan; Li, Zhi; Shao, Yameng; Chen, Lei; Yang, Yu; Xi, Jianning; Chen, Minglong; Jiang, Tingbo (Frontiers in Cardiovascular Medicine, 2022)
Objectives Cardiac magnetic resonance imaging (CMR) can be used for a one-step evaluation of myocardial function and pathological features after acute ST-elevation myocardial infarction (STEMI). We aimed to evaluate the value of fast microvascular occlusion (MVO) identification from contrast-enhanced steady-state free precession (CE-SSFP) combined with myocardial strain in predicting major cardiovascular adverse events (MACEs) in primary percutaneous coronary intervention (pPCI) patients with STEMI. Methods In total, 237 patients with STEMI who received pPCI and completed CMR scans within the following week were enrolled, MVO identification and the myocardial strain analysis were performed in CE-SSFP images without an additional method. The primary endpoint was the presence of MACE, which is defined as a composite of death, reinfarction, and congestive heart failure (HF). Results After 13 months of follow-up [interquartile range (IQR): 11–24], 30 patients (14%) developed MACE; the MVO (hazard ratio (HR) was 3.10; 95% CI: 1.14–8.99, p = 0.028), and the infarct size (IS) (HR: 1.03; 95% CI: 1.0–1.06, p = 0.042) and global longitudinal strain (GLS) (HR: 1.08; 95% CI: 1.01–1.17, p = 0.029) were finally associated with MACE. Receiver operating characteristic (ROC) analyses show that the area under the curve (AUC) of GLS was large (0.73 [95% CI, 0.63–0.82], p = 0.001), and the best cut-off was −11.8%, with 76.7% sensitivity and 58.9% specificity, which are greater than those of IS (0.70, 95% CI, 0.60–0.81, p < 0.001) and MVO (0.68, 95% CI, 0.58–0.78, p < 0.001). However, combining MVO and GLS resulted in a much greater finding (AUC = 0.775, 95% CI: 0.727–0.824, p < 0.001) and better sensitivity and specificity (83.3%, 66.5%). Conclusion Microvascular occlusion identification from contrast-enhanced cine combined with myocardial strain could be a quick and reliable option for patients with STEMI who underwent pPCI; it correlates well with the prognosis of patients with STEMI in terms of MACE.